2009
DOI: 10.1017/s0272263109990027
|View full text |Cite
|
Sign up to set email alerts
|

More on the Effects of Explicit Information in Instructed Sla

Abstract: The role of explicit information (EI) as an independent variable in instructed SLA is largely underresearched. Using the framework of processing instruction, however, a series of offline studies has found no effect for EI (e.g., Benati, 2004; Sanz & Morgan-Short, 2004; VanPatten & Oikkenon, 1996). Fernández (2008) presented two online experiments with mixed results. She found an effect for EI with processing instruction on one target structure (subjunctive in Spanish) but not the other structures (object prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 24 publications
(49 reference statements)
8
67
0
Order By: Relevance
“…L1-L2 form-meaning mapping differences. Our evidence therefore supports the points raised by the opening quotation (Henry, Culman and VanPatten, 2009): that the effectiveness of EI seems dependent on the nature of the EI, the target structure, and processing problem.…”
Section: Observation Of Online Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…L1-L2 form-meaning mapping differences. Our evidence therefore supports the points raised by the opening quotation (Henry, Culman and VanPatten, 2009): that the effectiveness of EI seems dependent on the nature of the EI, the target structure, and processing problem.…”
Section: Observation Of Online Effectssupporting
confidence: 88%
“…'Weaker' accounts suggest that learners can use EI to segment or parse the input (Terrell, 1991), notice features (Schmidt, 1990), understand a rule and help production (Leow, 2015), and arrive at correct interpretations with fewer practice items (Henry et al, 2009 4 ! to depend on several factors, including its precise nature Ð the type of information conveyed and the feature in focus.…”
Section: L2 Ei and Practicementioning
confidence: 99%
“…Some earlier PI studies (for instance, Culman et al, 2009;Fernandez, 2008;Henry et al, 2009;VanPatten et al, 2013) had also compared PI+EI to PI-EI groups, and all found that the effect of EI depended on the nature and complexity of the structure. For example, "EI was beneficial for the correct processing of the subjunctive" (Fernandez, 2008, p. 595), "explicit information speeds up the processes underlying acquisition" (Culman et al, 2009, p. 28), and "EI does have a facilitative effect for L2 German learners with PI" (Henry et al, 2009, p. 571).…”
Section: Discussionmentioning
confidence: 99%
“…All these studies found different results from those of VanPatten and Oikkenon (1996); that is, they reported a superior effect of the PI+EI group over PI-EI, thereby revealing a significant effect for EI, as well as that of structured input, in PI. In these studies, EI was found to play a facilitative role in PI, and therefore it was suggested to be beneficial in PI for different language features; this, however, depends on the nature of the tasks and the associated processing problem (Farley, 2004a;Fernandez, 2008;Henry et al, 2009). Botana (2013) also favoured the provision of EI for task-essential activities in PI, as "knowledge derived from EI-based treatments can be and often is a necessary precursor for any other more automatized knowledge to ever be possible" (p. 164).…”
Section: Processing Instruction and Explicit Informationmentioning
confidence: 99%
“…Although processing instruction often provides explicit information as part of the treatment, research on processing instruction has repeatedly shown that this information is not needed. Structured input alone is sufficient to cause changes in learner knowledgewhich is predicted by the very nature of acquisition (i.e., input + processors + UG) (see, for example, Fernández, 2008;Henry, Culman & VanPatten, 2009;Oikennon, 1996, andvarious papers in VanPatten, 2004a).…”
Section: I3 Is the Development Of Mental Representation Amenable To mentioning
confidence: 99%